Pharmacological Management of Insomnia in Parkinson's Disease - Popławska-Domaszewicz, Karolina; Metta, Vinod; Chen, Rosabel; Falup-Pecurariu, Cristian; Wu, Kit; Chaudhuri, K Ray (Sleep medicine clinics, 2025)
Sleep dysfunction can affect almost 90% of Parkinson's disease (PD) patients and insomnia related to fragmented sleep is common. Satisfactory management remains an unmet need although dopaminergic non-oral treatments utilising a continuous drug delivery strategy appears to help sleep maintenance insomnia. Transdermal therapy with rotigotine or subcutaneous apomorphine infusion is effective while recent data show considerable efficacy of intrajejunal or subcutaneous levodopa infusion on alleviation of insomnia in PD. Pharmacologic management of sleep onset insomnia remains suboptimal and options range from cautious use of sedatives and hypnotics to management of comorbid factors, such as psychosis and depression.